2004
DOI: 10.1103/physrevc.70.044311
|View full text |Cite
|
Sign up to set email alerts
|

β-delayed proton decay of a high-spin isomer inA94g

Abstract: The decay of the ͑7 + ͒ and ͑21 + ͒ isomers of the N = Z isotope 94 Ag was studied at the GSI on-line mass separator by measuring ␤-delayed protons, ␥ rays, proton-␥ and proton-␥-␥ coincidences as well as the ␤-strength distribution. We have observed high-spin (up to 39/ 2) states in 93 Rh populated by proton emission following the ␤ decay of the 94 Ag isomers. The major part of the population is related to the ␤ decay of the known ͑7 + ͒ isomer whose half-life is 0.61͑2͒ s. The assignment of the high-spin ͑21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 20 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…Because of the recent experimental successes, the highspin I π = 21 + and low-spin 7 + isomers in the odd-odd N = Z nucleus 94 Ag have become a discussion focus [8,9,10,11]. In this nucleus, the high-spin 21 + isomer has a high excitation energy of 6.7 (5) MeV with a notably long half-life of 0.39(4) s, and is open to β, one-proton, and two-proton decays [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the recent experimental successes, the highspin I π = 21 + and low-spin 7 + isomers in the odd-odd N = Z nucleus 94 Ag have become a discussion focus [8,9,10,11]. In this nucleus, the high-spin 21 + isomer has a high excitation energy of 6.7 (5) MeV with a notably long half-life of 0.39(4) s, and is open to β, one-proton, and two-proton decays [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In this nucleus, the high-spin 21 + isomer has a high excitation energy of 6.7 (5) MeV with a notably long half-life of 0.39(4) s, and is open to β, one-proton, and two-proton decays [12,13]. Although the shell model calculations with the empirical effective interaction in the restricted (1p 1/2 , 0g 9/2 ) model space could reproduce the energy levels and high-spin isomers in 95 Ag, 95 Pd, and 94 Pd, it failed to predict the isomerism of 21 + state in 94 Ag [9,10]. On the other hand, it has been shown that the large-scale shell model calculations with the extended model space (0g 9/2 , 1d 5/2 , 0g 7/2 , 1d 3/2 , 2s 1/2 ) can obtain a 21 + -19 + level inversion, which suggests that the core excitations across the 100 Sn shell-closure play a crucial role in generating the 21 + isomer with such a long halflife [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among the relevant topics are the robustness of the N = Z = 50 shell closures in 100 Sn and the superallowed Gamow-Teller decay [1]; the limit of bound N = Z heavy nuclei and the location of the proton dripline; the role of T = 0 proton-neutron (pn) interactions in contrast isomers in 94 Ag, 96 Cd, and 98 In [3,[13][14][15][16][17][18][19]; and core-excited isomers in 96 Ag and 98 Cd [20][21][22]. This is by no means an exhaustive list.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]). The influence of the high-spin g 9/2 single-particle orbital on the valence nucleon or hole structure and the proton-neutron interactions enhanced in N ≈ Z nuclei [7], lead to a broad range of spin and seniority effects including isomers [8], which can be sensitive probes of nuclear structure.…”
mentioning
confidence: 99%